2021
DOI: 10.3390/jcm10020282
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Neurophysiological Aspects of Inhibition—The Effects of Acute Cardiovascular Exercise

Abstract: This review summarizes behavioral and neurophysiological aspects of inhibitory control affected by a single bout of cardiovascular exercise. The review also examines the effect of a single bout of cardiovascular exercise on these processes in young adults with a focus on the functioning of prefrontal pathways (including the left dorsolateral prefrontal cortex (DLPFC) and elements of the prefrontal-basal ganglia pathways). Finally, the review offers an overview on the potential effects of cardiovascular exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 115 publications
(184 reference statements)
1
13
0
1
Order By: Relevance
“…3,9 Thus, the present findings build upon previous studies of acute, exercise-induced neuroplasticity post-stroke, suggesting a shift from a generalized to a more specific effect on inhibition over time with repeated exposure to aerobic exercise training. The present inhibitory specificity of habitual exercise training in stroke is consistent with previous reports in neurotypical populations of young 11,12,43 and older adults. 4446 For example, older adults with and without Parkinson’s disease demonstrated selectively improved cognitive inhibitory control following a 3-month aerobic exercise intervention.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…3,9 Thus, the present findings build upon previous studies of acute, exercise-induced neuroplasticity post-stroke, suggesting a shift from a generalized to a more specific effect on inhibition over time with repeated exposure to aerobic exercise training. The present inhibitory specificity of habitual exercise training in stroke is consistent with previous reports in neurotypical populations of young 11,12,43 and older adults. 4446 For example, older adults with and without Parkinson’s disease demonstrated selectively improved cognitive inhibitory control following a 3-month aerobic exercise intervention.…”
Section: Discussionsupporting
confidence: 92%
“…9,10 Among several domains of cognitive executive function (e.g., response inhibition, response facilitation, cognitive flexibility, planning and execution), aerobic exercise may most strongly benefit response inhibitory control that engages inhibitory cortical networks. [11][12][13][14] The potential for aerobic exercise to improve inhibitory control is of particular interest in people after stroke who demonstrate degraded cortical inhibitory function, [15][16][17][18] which is linked to cognitive and motor dysfunction. [15][16][17][18] Given the well-established benefits of aerobic exercise for cardiovascular health, the effect of exercise training on persistent behavioral deficits and the dysfunctional cortical neurophysiology underlying these deficits after stroke remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…However, over the last decade there has been a rapid increase in evidence demonstrating that regular patterns of human behaviour have major effects on neurocognitive systems ( Levin, Netz & Ziv, 2021 ; Stillman et al, 2016 ). With this insight has come growing interest in the capacity of behavioural interventions, such as cognitive training and physical training, to potentially improve inhibitory control.…”
Section: Introductionmentioning
confidence: 99%
“…Given the demographic development in modern societies, understanding and preventing this decline, even supporting adaptive processes, are of outmost importance. For example, it has been suggested that physical exercises and non-invasive brain stimulation of prefrontal cortex could modulate inhibitory interactions (Verstraelen et al 2020 ; Levin et al 2021 ), which might improve not only bimanual movement control but also inhibitory control in general in older adults.…”
Section: Discussionmentioning
confidence: 99%